E government technology transfer: a case study of the implementation of a European patent management system in Brazil - Cavalheiro, Gabriel Marcuzzo do Canto; Joia, Luiz Antonio (2016)
In order to bolster the emerging but still underdeveloped conceptualization of e-government technology transfer, we examine the implementation of a European Patent Management System in Brazil. The case study provided in this article offers opportunities to improve understanding on technical and organizational issues associated with e-government technology transfer. Our findings provide evidence that the transfer of e-government technology from a European to a Brazilian context requires multiple adaptations of the original design, intensive learning on the side of the recipient organization, and flexible implementation plans. - Reproduced.
Keywords: Patents; Technology transfer; E governance